Identification of Eukaryotic Translation Elongation Factor 1-α 1 Gamendazole-Binding Site for Binding of 3-Hydroxy-4(1 H)-quinolinones as Novel Ligands with Anticancer Activity - Burglová, Kristyna; Rylová, Gabriela; Markos, Athanasios; Prichystalova, Hana; Soural, Miroslav; Petracek, Marek; Medvedikova, Martina; Tejral, Gracian; Sopko, Bruno; Hradil, Pavel; Dzubak, Petr; Hajduch, Marian; et al. (Journal of medicinal chemistry, 2018)
Here, we have identified the interaction site of the contraceptive drug gamendazole using computational modeling. The drug was previously described as a ligand for eukaryotic translation elongation factor 1-α 1 (eEF1A1) and found to be a potential target site for derivatives of 2-phenyl-3-hydroxy-4(1 H)-quinolinones (3-HQs), which exhibit anticancer activity. The interaction of this class of derivatives of 3-HQs with eEF1A1 inside cancer cells was confirmed via pull-down assay. We designed and synthesized a new family of 3-HQs and subsequently applied isothermal titration calorimetry to show that these compounds strongly bind to eEF1A1. Further, we found that some of these derivatives possess significant in vitro anticancer activity.
Keywords: lidé; vztahy mezi strukturou a aktivitou; Cell Line, Tumor; Antineoplastic Agents; Molecular Conformation; Quinolones; protinádorové látky; Humans; Binding Sites; Indazoles; indazoly; Computational Biology; výpočetní biologie; Structure-Activity Relationship; elongační faktor 1; Peptide Elongation Factor 1; nádorové buněčné linie; molekulární modely; chinolony; ligandy; Ligands; vazebná místa; Models, Molecular; molekulární konformace